Efficacy, safety, and immunogenicity of the human papillomavirus 16/18 AS04-adjuvanted vaccine in women older than 25 years: 7-year follow-up of the phase 3, double-blind, randomised controlled VIVIANE study. Issue 10 (October 2016) - Wheeler, Cosette M; Skinner, S Rachel; Del Rosario-Raymundo, M Rowena; Garland, Suzanne M; Chatterjee, Archana; Lazcano-Ponce, Eduardo; Salmerón, Jorge; McNeil, Shelly; Stapleton, Jack T; Bouchard, Céline; Martens, Mark G; Money, Deborah M; et al.
Summary: Background: Although the risk of human papillomavirus (HPV) infection is greatest in young women, women older than 25 years remain at risk. We present data from the VIVIANE study of the HPV 16/18 AS04-adjuvanted vaccine in adult women after 7 years of follow-up. Methods: In this phase 3, double-blind, randomised controlled trial, healthy women older than 25 years were enrolled (age stratified: 26–35 years, 36–45 years, and ≥46 years). Up to 15% in each age stratum had a history of HPV infection or disease. Women were randomly assigned (1:1) to receive HPV 16/18 vaccine or aluminium hydroxide control, with an internet-based system. The primary endpoint was vaccine efficacy against 6-month persistent infection or cervical intraepithelial neoplasia grade 1 or greater (CIN1+) associated with HPV 16/18. We did analyses in the according-to-protocol cohort for efficacy and total vaccinated cohort. Data for the combined primary endpoint in the according-to-protocol cohort for efficacy were considered significant when the lower limit of the 96·2% CI around the point estimate was greater than 30%. For all other endpoints and cohorts, data were considered significant when the lower limit of the 96·2% CI was greater than 0%. This study is registered withClinicalTrials.gov, numberNCT00294047 . Findings: The first participant was enrolled on Feb 16, 2006, and the last study visit took place on Jan 29, 2014. 4407 women were in the according-to-protocol cohort for efficacy (n=2209 vaccine, n=2198 control) and 5747 women in the total vaccinated cohort (n=2877 vaccine, n=2870 control). At month 84, in women seronegative for the corresponding HPV type in the according-to-protocol cohort for efficacy, vaccine efficacy against 6-month persistent infection or CIN1+ associated with HPV 16/18 was significant in all age groups combined (90·5%, 96·2% CI 78·6–96·5). Vaccine efficacy against HPV 16/18-related cytological abnormalities (atypical squamous cells of undetermined significance and low-grade squamous intraepithelial lesion) and CIN1+ was also significant. We also noted significant cross-protective efficacy against 6-month persistent infection with HPV 31 (65·8%, 96·2% CI 24·9–85·8) and HPV 45 (70·7%, 96·2% CI 34·2–88·4). In the total vaccinated cohort, vaccine efficacy against CIN1+ irrespective of HPV was significant (22·9%, 96·2% CI 4·8–37·7). Serious adverse events related to vaccination occurred in five (0·2%) of 2877 women in the vaccine group and eight (0·3%) of 2870 women in the control group. Interpretation: In women older than 25 years, the HPV 16/18 vaccine continues to protect against infections, cytological abnormalities, and lesions associated with HPV 16/18 and CIN1+ irrespective of HPV type, and infection with non-vaccine types HPV 31 and HPV 45 over 7 years of follow-up. Funding: GlaxoSmithKline Biologicals SA.